Technopolitical, decolonial, and feminist pedagogies: the Radio CINEF experience as a territory of struggle for youth. - Garcia Ramirez, Nancy Lizbeth (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
What is proposed here is an epistemological, ethical, and political commitment to inhabiting digital practices with awareness and creativity, with the intention of politicizing technologies without disembodiment. It is based on the premise that there is a need to build pedagogies of encounter to dismantle the matrix of oppressions. Therefore, this text invites us to understand podcasting, through the experience of Radio CINEF, as a pathway that fosters activism with and from youth, through technopolitical, decolonial, and feminist intervention.